Pengaruh Gaya Kepemimpinan Transformasional, Motivasi, Burnout terhadap Kepuasan Kerja dan Kinerja Karyawan - Agusthina Risambessy; Bambang Swasto; Armanu Thoyib; Endang Siti Astuti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Changes in organizational structure, vision and changes leadership is inevitable in any institution. Leadership style is a special characteristic that distinguishes a leader from one another and this is a powerful force to move the employee or employees in completing work towards the achievement of maximum results, especially in improving public health services in environment compete. This study aimed to describe and analyze the influence of leadership styles, motivation, burnout, and job satisfaction and employee performance. The unit of analysis is nursing paramedic at a hospital in Malang Raya. Data collection techniques: conduct interviews using questionnaires and observation techniques as well as using SEM analysis tool with 105 respondents in a Hospital of Malang Raya.The research proves that: there was a significant effect between transformational leadership styles on motivation, burnout, on job satisfaction, on employee performance. There was a significant and negative influence between motivations toward burnout, on job satisfaction, on employee performance. Burnout has significant influence and negative impact on job satisfaction, on employee performance. There is significant influence between job satisfactions to employee performance. This research proved that burnout can occur in a hospital paramedic of Malang Raya.Keywords: Transformational Leadership Style, Motivation, Burnout, Job Satisfaction and Employee Performance